Acaricide activity of Piper macedoi Yunck essential oil against Rhipicephalus sanguineus (Research, Society and Development, 2022)
This study evaluated the acaricide efficacy of Piper macedoi essential oil on larvae of ticks of the species Rhipicephalus sanguineus. The essential oil was extracted by hydrodistillation in a Clevenger-type apparatus. The test consisted of six treatments: from the group I to IV, samples corresponded to different concentrations of essential oil (500 μg.mL-1; 250 μg.mL-1; 100 μg.mL-1 and 50 μg.mL-1) diluted in Tween 80 at 2%. Groups V and VI corresponded to the negative controls (with distilled water and Tween 80 to 2%) and the positive control (with acaricide Amitraz at 12.5%), respectively. The essential oil was rich in apiole (39.81%) and dillapiole (26.47%). The essential oil of P. macedoi presented an activity against the larvae of R. sanguineus, with a better efficiency observed for concentrating 500 μg.mL-1, mortality of 80.67%, indicating a dose-dependent response.